Molecular diversity and prevalence of Helicobacter, Bartonella and Streptococcus in Mus musculus from sub-Antarctic Marion Island in relation to host diversity - Bastos, Armanda D.S. (University of Pretoria, 2013)
Dissertation (MSc)--University of Pretoria, 2012.